ContHeart : software for monitoring isolated cardiomyocyte shortening - Fagundes, Daniel Leal (2020)
ContHeart is a software designed to analyze cardiomyocyte contractile dynamics using Canny’s method for edge detection in recorded videos. It is a tool that allows researchers (users) to post-analyze video usually captured in their work routine, without special capture apparatus. The software has a user-friendly graphical interface in which the user can apply filters and modify parameters to optimize edge detection and shortening measurement. Therefore, the software quickly generates reliable data on the variation of cell dimensions over time, which can be interpreted by the researcher. We believe researchers will find here a powerful tool to enhance the reach of their basic cardiovascular research, allowing them to include the cardiomyocytes shortening analysis on their work. That might increase the scope of knowledge within the field, as the effect of different pathophysiological conditions may be analyzed on cardiomyocyte contraction.